Preparation of [Fe(paptH)2] (CF3SO3)2 and [Fe(paptH)2] [Fe(CN)5NO] (paptH = bis(2-(pyridin-2-ylamino)-4-(pyridin-2-yl)thiazole: Magnetic, Mössbauer, and Electronic Spectral Properties - Kristian Handoyo Sugiyarto; Harold Andrew Goodwin (Universitas Jenderal Soedirman, 2022)
Complexes of [Fe(paptH)2][X]2.nH2O, (paptH = 2-(pyridin-2-ylamino)-4-(pyridin-2-yl)- thiazole, X = CF3SO3 and n = 1.5, and X2 = [Fe(CN)5NO] and n = 3) have been characterized in magnetic, Mössbauer, and electronic spectral properties. The studies reveal that the two complexes are predominantly quintet state at room temperature, but singlet at low temperature (below 91K). The change is assigned as a thermally spin state transition, singlet 1A1g (LS, low-spin) ↔ quintet 5T2g (HS, high-spin), in iron(II), being gradual, continuous, and incomplete at the experimental temperature range, and without hysteresis in these instances. The two complexes were yellowish brown at room temperature ( 298K) but darkening to reddish brown at the lower temperatures.